Pendidikan dan Pelatihan Ergonomi bagi Pekerja untuk Meningkatkan Efisiensi dan Kualitas Kerja dalam Sistem Produksi Industri - Muhamad Noval; Siti Nur Hamidah; Ikbal Anggara (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2024)
In modern industrial production systems, ergonomics training is essential for balancing productivity demands with worker health. For example, 36–50% of Indonesian manufacturing workers report work-related musculoskeletal complaints (e.g., 55.36% prevalence of back/neck pain). This study investigates an integrative ergonomics education intervention, combining anthropometry, biomechanics, and cognitive psychology principles. Using a quantitative experimental design, industrial workers attended a webinar consisting of theoretical and hands-on sessions on ergonomic principles. Post-training assessments show that the intervention reduced musculoskeletal complaints by 42.92% and increased production capacity by 40.03%. Ergonomic workstation redesign further improved overall equipment effectiveness (OEE) from 61.2% to 77.9%. Additionally, ergonomic lifting training on a production line cut process errors by 30%, raising first-pass yield from 63% to 93%. Kirkpatrick evaluation (reaction and behavior levels) revealed that 66.7% of participants reported high satisfaction and 85% sustained ergonomic behavior adoption after three months. By targeting both physical and cognitive job demands, the training aligns with lean production principles and promotes sustainable efficiency gains. The intervention also achieved a 1:4.2 return on investment and a 35% reduction in musculoskeletal injury costs. These findings demonstrate that evidence-based ergonomics training can substantially improve worker health and production efficiency, providing a multidisciplinary framework that bridges classical ergonomics theory with Industry 4.0 challenges.